ANALISIS PENGARUH NILAI PELANGGAN,KUALITAS PELAYANAN DAN HUBUNGAN EMOSIONAL TERHADAP LOYALITAS NASABAH (Studi Kasus pada Bank Riau Kepri Cabang Pembantu Batu Aji) - Burhan B; Edwin Agung Wibowo; Rahman Hasibuan (Universitas Riau Kepulauan, 2015)
Research on Effect Analysis Customer Value, Service Quality and Customer Loyalty Toward Emotional Connection Bank Riau Kepri Batu Aji branch in Batam. This study aimed to examine the impact of service quality and customer loyalty emotional connection.Based on the results of this study using a sample of 100 respondents who are customers of the Bank Riau Kepri Batu Aji branches personality using indicators that are valid and reliable shows the influence of each variable customer value, quality service and an emotional connection to the customer loyalty. For the expected future need for improved quality of care in order to better improve customer loyalty.